GREAT Teaching Revolution through Gamification-AI-EdTech Training Realizing Mindful-Joyful Learning: GREAT Teaching Revolution Melalui Pelatihan Gamifikasi-AI-EdTech Mewujudkan Mindful-Joyful Learning - Ningsih, Purnama; Anggreni, Afrillia; Agussatriana, Agussatriana; Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
21st century educational transformation requires teachers to be adaptive in using technology in learning. In general, teachers at SMAN 9 Palu still face limitations in effectively integrating technologies such as gamification, AI, and EdTech. Therefore, this community service was conducted with the aim of providing training and practice in developing technology-based learning tools and deep learning approaches (Joyful and mindful learning) using AI, EdTech, and gaming applications. The results of the community service activities were evaluated from pre-tests and post-tests given to participants. The evaluation results consisted of 8 aspects, including understanding of joyful and mindful learning, knowledge of gamification in learning, utilization of Artificial Intelligence (AI) in learning, use of Educational Technology (EdTech), readiness to innovate in the learning process, creativity in designing learning media and activities learning activities, reflective experiences in learning, and expectations regarding the training, showing an increase from the “fair” category to the “very high” category.